A Road to the Recognition of Home-Workers: Transformation of POS Production Modes and Roles of Home-workers in Batik Industry in Central Java (Case Study in Cluster Batik in Central Java) - Hunga , Arianti Ina R. (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2018)
Home-work (HW) in the putting-out system (POS)-based industry is the real proof of global capitalism existence in domestic space. It utilizes house resources and manipulates the domestic area to keep production costs low in order to compete in the global market. POS and HW become paradoxical as they are widely employed and categorized as strategic commodity production, market their products to the global market, and involve certain skills, creativity and technology. Nevertheless, the facts are obscured from public eyes. Efforts to uncover the obscured facts have been done through POS and HW transformation strategies, which are described in this paper. The paper aims at promoting POS and HW into public areas. The data used were gathered through participatory action research on batik industry based on